Changes in the hormonal profile of athletes following a combat sports performance - Ziemba, A.; Adamczyk, J. G.; Barczak, A.; Boguszewski, D.; Kozacz, A.; Dabrowski, J.; Steczkowska, M.; Peplonska, B.; Zekanowski, C. (BioMed Research International, 2020)
Background and Study Aim. Stimulation of the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis are a crucial mechanism of adaptation to physical exercise, in particular in combat sports. This study assesses changes of the relevant hormonal profiles upon performance in selected combat sports. Material and Methods. Participants (130 men practicing combat sports at a high level) were divided by discipline: karate (K), taekwondo (T), and judo, wrestling, and sumo combined (JWS). Blood concentration of adrenaline, noradrenaline, cortisol, testosterone, and brain-derived neurotrophic factor (BDNF) was determined before and after fighting. Results. Following fighting, the adrenaline concentration was significantly higher in all athletes, most markedly in K (). Baseline cortisol and BDNF levels did not differ among the groups and rose significantly in all the groups after the performance. Baseline testosterone concentration was slightly higher in K than in JSW and rose in all the groups to reach similar levels; the increase in T was significantly higher than in K. Conclusions. Despite substantial differences in the characteristics of the combat sports investigated, including the type of physical effort and the required balance between restraint and aggression, the performance in each of them gives rise to similar hormonal changes with a possible exception of karate showing higher stress hormone levels.